Development of Mass-Based Road Public Transportation With Buy the Service Scheme Yogyakarta City - Ardiansyah, Ahmad; Handayani, Susanty; Widodo, Erna S. (Dinasti Publisher, 2025)
The rapid growth of urban areas requires the provision of adequate transportation infrastructure so that the mobility of people and goods can run optimally. Complex urban transportation problems require appropriate solutions to support economic development, activities, and transportation movements. Successful transportation development is essential to increase ease of movement, which impacts on the efficiency of time and place. Mass public transport has great economic, social and environmental benefits, but this need has not been met equally. Public transport, as an important part of the national transportation sector, is key in realizing better mobility. One proposed solution is a road-based mass transit purchasing scheme, which can meet transportation needs in a more affordable and sustainable way. The existence of mass transit is particularly relevant in cities characterized by tourism, such as Yogyakarta, to support the tourism sector and the city's economy. Therefore, the development of a physically integrated transportation system, fares, and schedules is necessary to achieve this goal. This research uses quantitative and qualitative mixed methods. The results show that a Buy The Services scheme in road-based mass transit can improve service quality and attract more passengers, provided that the facilities desired by users are in line with their ability to pay. The operational performance of public transportation in Yogyakarta, such as Trans Jogja, has met the Minimum Service Standards (MSS), with good quality indicators. Setting tariffs in accordance with users' ability and desire is important to maintain accessibility and sustainability of services, as well as ensuring optimal operational quality.